The impact of democratic leadership style on job performance in the Cement Industry - Dara Jupita Febriany; Justine Tanuwijaya; B Medina Nilasari (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effects of talent development, talent retention, democratic leadership style, and transformational leadership style on job performance, with job satisfaction as a mediating variable among employees of cement industry. A quantitative research design was employed using survey data collected from 188 employees. The proposed relationships were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results indicate that talent development, talent retention, and democratic leadership style have positive and significant effects on both job performance and job satisfaction. In contrast, transformational leadership style does not have a significant effect on either job performance or job satisfaction. Furthermore, job satisfaction does not significantly influence job performance and fails to mediate the relationships between the independent variables and job performance. These findings suggest that employee performance is enhanced primarily through direct organizational practices related to talent management and participative leadership rather than through indirect motivational mechanisms. The study contributes to the human resource management literature by clarifying the relative effectiveness of talent management and leadership approaches in improving employee performance and offers practical implications for organizations seeking to strengthen workforce performance through evidence-based human resource strategies. Keywords: Talent; Retention; Leadership; Satisfaction; Performance